Hydrological and mechanical properties of loess landslides under different vegetation restoration types (Bangladesh Journal of Botany, 2021)
Loess landslide is a common geological disaster in northern Shaanxi, which seriously affects people's life and property safety and social and economic development. The research on vegetation restoration types and hydrological and mechanical properties of loess landslides can provide basic data support for landslide stability prediction, and further provide reference for landslide prevention and treatment. In the present study, the loess landslide point of Zhang Zi Gou in Gan Quan County, Yan’an City was taken as the research object. On the basis of the existing natural condition data, the basic physical and mechanical properties and hydrological characteristics were obtained by collecting field landslide soil samples for indoor experimental analysis. The indoor analysis shows that the landslide is mainly distributed in dry land, medium coverage and low coverage grassland, indicating that the surface vegetation coverage can affect the stability of landslide. The worse the vegetation coverage, the more landslides occur. The void ratio and porosity of landslide soil decrease with the increase of dry density. The cohesion of natural soil is obviously higher than that of saturated soil, and the internal friction angle of natural soil is slightly lower than that of saturated soil. In general, due to the influence of water content, the shear strength of natural soil samples is higher than that of saturated soil samples. Therefore, in order to improve the accuracy of prediction and early warning system, it is necessary to consider the response of hydrological and mechanical properties of loess to vegetation restoration. The results provide basic data support for the establishment of loess landslide stability prediction system and provide reference for geological disaster management.Bangladesh J. Bot. 50(3): 795-801, 2021 (September) Special